2013
DOI: 10.5301/hipint.5000024
|View full text |Cite
|
Sign up to set email alerts
|

Cementless Bipolar Hemiarthroplasty Using a Rectangular Cross-Section Stem for Unstable Intertrochanteric Fractures

Abstract: The purpose of this study was to compare the clinical and radiographic results for elderly patients sustaining unstable intertrochanteric fractures treated with an uncemented bipolar hemiarthroplasty using a double-tapered, rectangular cross-section stem. Thirty-seven patients (21 females, 16 males; mean age 73.5 years, range 65-88 years) who underwent bipolar hemiarthroplasty with a standard (double-tapered, rectangular cross-section) uncemented stem were followed up for a minimum of two years. At final follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Results from recent reports demonstrated that primary bipolar hemiarthroplasty allowed patients to ambulate earlier with a low failure ratio. [29,30] And cut-out complication rates with newer design intramedullary nails were lower. [31] Although the technology of the IMF was continuously improved, the systematical review by Norris et al [32] reported that the incidence of a 2nd fracture after IMF was approximately 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Results from recent reports demonstrated that primary bipolar hemiarthroplasty allowed patients to ambulate earlier with a low failure ratio. [29,30] And cut-out complication rates with newer design intramedullary nails were lower. [31] Although the technology of the IMF was continuously improved, the systematical review by Norris et al [32] reported that the incidence of a 2nd fracture after IMF was approximately 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the cementless stem has been widely used for hip arthroplasty and there have been many studies reporting good results for unstable intertrochanteric fractures [3][4][5][6][7][8][9]. However, studies evaluating the long-term outcomes patients who have survived for over five years or femoral stems applied using different fixation methods according to each design have been small studies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, if the type 3C stem is used for intertrochanteric fractures in which the proximal region is fractured, the bone ongrowth of the proximal region may be poorer because the fixation force is mainly obtained in the diaphysis and stable three-point fixation cannot be achieved. Some studies have reported good results with type 3C stems for unstable intertrochanteric fractures [3,7]. However, studies that report excellent results using these type 3C stems have been mostly short-term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations